Relationships Between Marital Stress, Depressive Symptoms, Psychache and Infertility Among Couples in Fertility Treatment, in Port Harcourt Nigeria. - Maduka, Ada Ume; Okoye, Chukwuemeka A.F (Social Science Research, 2024)
The effects of Psychache, depressive symptoms and marital stress are notable in the life of infertile couples. Therefore, the study examined the relationship between marital stress, depressive symptoms, psychache and infertility among couples undergoing fertility treatment in Port Harcourt, Rivers State, Nigeria. One hundred and forty four (144) participants were drawn, using convenience sampling. The Symptoms Distress Checklist, Marital Stress Inventory and Psychache Scale were intruments used for data collection. The sample comprised 93.8% females and 6.2% males, with age range of 18 to 50 years, mean age of 1.97 and standard deviation of .14. Survey design and correlational design, using Pearson Product Moment Correlation Coefficient statistics were used for data analysis. Significance was accepted at P <.05. The study revealed a significant relationship between marital stress and infertility at (M= 2.00, Std.D = .029, .019, .013, F =.000, df = 4, 1, Sig = .000 P<.05). The study also revealed that depressive symptoms had a positive relationship with infertility at (M= 1.78, 2.00, Std.D = .035, .019, F =13.488, df = 1, 1, Sig = .000 P<.05). The finding of the result also showed a positive relationship between psychache and infertility at (M= 2.00, 1.78, Std.D = .029, .035, F =.000, 13.488, df = 4, 1, Sig = .000 P<.05). It was recommended among others, that developing effective psychache intervention programmess for diverse infertility issues will help couples adjust better.